0
$\begingroup$

Compute explicitly $S_n(x)$, the $n^{th}$ partial sum of the series

$$\sum_{k=1}^∞ \frac{x\left[-1+4k(k+1)x^2\right]}{(1+4k^2x^2)(1+4(k+1)^2x^2)}$$

then compute the sum $S(x)$ of the infnite series, and prove that, for $a > 0$, the series is not uniformly convergent on $(a, a)$, but is uniformly convergent on $(a, ∞)$

My attempt:

$$S_n(x) = \sum_{k=1}^∞ \frac?{1+4k^2x^2} - \frac?{1+4(k+1)^2x^2}$$ which is a telescoping series.

And then, having formed $S_n(x)$, I find $S(x)$ = $\lim_{n→∞} S_n(x)$.

Finally, I find $M_n = \sup|S_n(x) - S(x)|$ and if $\lim_{n→∞} M_n$ = $0$, then it converges uniformly. My problem is in the first step. I don't know how to compute $S_n(x)$ explicitly.help please? This is my attempt for partial fraction decomposition

$\endgroup$
  • $\begingroup$ Do you know how to do partial fraction decomposition? $\endgroup$ – Clayton May 13 at 11:34
  • $\begingroup$ @Clayton yes I do $\endgroup$ – pascale bou chahine May 13 at 11:43
  • $\begingroup$ When you tried it here, did anything go wrong? $\endgroup$ – Clayton May 13 at 11:47
  • $\begingroup$ @Clayton I'm gonna try it now and let you know $\endgroup$ – pascale bou chahine May 13 at 11:49
  • 1
    $\begingroup$ The numerators in a partial fraction decomposition have to have a degree one less than the denominators, so the numerator of the first fraction should be $dx+e$ and the second $fx+g$. That gives you enough parameters. It looks to me like $e=g=0$ because the denominators have only even powers of $x$ and the numerators only odd. $\endgroup$ – Ross Millikan May 13 at 13:36
0
$\begingroup$

Based on the discussion in the comments we are trying to do a partial fraction decomposition$$\frac{x\left[-1+4k(k+1)x^2\right]}{(1+4k^2x^2)(1+4(k+1)^2x^2)}=\frac{ax+b}{1+4k^2x^2} - \frac{cx+d}{1+4(k+1)^2x^2}\\=\frac{(ax+b)(1+4(k+1)^2x^2)-(cx+d)(1+4k^2x^2)}{(1+4k^2x^2)(1+4(k+1)^2x^2)}\\ -x+4k(k+1)x^3=(ax+b)(1+4(k+1)^2x^2)-(cx+d)(1+4k^2x^2)\\b+d=0\\4(k+1)^2b+4k^2d=0\\b=d=0\\a-c=-1\\4(k+1)^2a-4k^2c=4k(k+1)\\4(k+1)^2a-4k^2(a+1)=4k(k+1)\\(2k+1)a-4k^2=4k(k+1)\\a=\frac {8k^2+4k}{2k+1}\\a=4k\\c=4k+1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.